PHYTOCHEMICAL SCREENING, ANTIMICROBIAL AND CYTOTOXICITY STUDIES OF ETHANOL LEAF EXTRACT OF APHANIA SENEGALENSIS (SAPINDACEAE) - Fall, Alioune Dior; Bagla, Victor P; Bassene, Emmanuel; Eloff, Jacobus Nicolaas (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Aphania senegalensis (Sapindaceae) is commonly used in Senegalese traditional medicine to treat pain, inflammation, asthenia, bacterial and fungal infections. The aim of this study was to determine the type of phytochemical constituents present in the ethanol leaf extract and its antimicrobial activity against selected bacterial and fungal pathogens. Materials and Methods: The ethanol leaf extract of A. senegalensis was evaluated for its cytotoxic effect in the MTT assay against Vero cells. Flavonoids and tannins were the main constituents of the ethanol leaf extract. Results: The extract inhibited the growth of the three fungal strains used in this study moderately with the lowest MIC obtained for Candida albicans (0.16 mg/mL). The extract also inhibited the growth of Aspergillus fumigatus and Cryptococcus neoformans with an MIC of 0.62 mg/mL. For bacterial pathogens, strong inhibition was obtained against Enterococcus faecalis (ATTC 29212) (MIC 0.08 mg/mL), while moderate inhibition was obtained for Escherichia coli (ATTC 25922) (MIC 0.16 mg/mL) and Staphylococcus aureus (ATTC 29213) (MIC 0.31mg/mL). The extract however did not inhibit the growth of Pseudomonas aeruginosa (ATTC 27853) at the highest concentration (2.5 mg/ml) tested. The ethanol leaf extract of A. senegalensis had a higher cytotoxicity than berberine used as the positive control (LC50 2.67±0.04 μg/mL and 9.99±0.54 μg/mL respectively). The best selectivity index values was obtained for Enterococcus faecalis (SI = 1.24), followed by Escherichia coli (SI = 0.62) for bacterial pathogens and C. albicans (SI = 0.62) for fungal pathogens. Conclusion: The findings of this study suggest that the extracts may not be safe for use in animals infected by some pathogens.Enterococcus faecalis (ATTC 29212) (MIC 0.08 mg/mL), while moderate inhibition was obtained for Escherichia coli (ATTC 25922) (MIC 0.16 mg/mL) and Staphylococcus aureus (ATTC 29213) (MIC 0.31mg/mL). The extract however did not inhibit the growth of Pseudomonas aeruginosa (ATTC 27853) at the highest concentration (2.5 mg/ml) tested. The ethanol leaf extract of A. senegalensis had a higher cytotoxicity than berberine used as the positive control (LC50 2.67±0.04 µg/mL and 9.99±0.54 µg/mL respectively). The best selectivity index values was obtained for Enterococcus faecalis (SI = 1.24), followed by Escherichia coli (SI = 0.62) for bacterial pathogens and C. albicans (SI = 0.62) for fungal pathogens. This indicatives that the extracts may not be safe to use on animals infected by some pathogens.